Unity and wasatiyyah as prerequisites in creating an exemplary society: a Rısalah An-Nur approach - Akhmetova, Elmira; Mansor Majdin, Mohamad Firdaus (2017)
This paper discusses the ideas of Bediuzzaman Said Nursi on unity and moderation, and suggests that the way of moderation is capable to create an exemplary society.